(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the history and specific aspects of Baroque art. Baroque art is an art style that developed and disappeared in Europe between the 17th and 18th centuries. Baroque represents a programmatic judgment distinguished by expressive, experiential and mythical sentiments, bright colors, dramatic style and connection. In this period, it was used to express modernity and completeness.